2012
DOI: 10.1177/1077801212474874
|View full text |Cite
|
Sign up to set email alerts
|

A Public Health Approach to Intimate Partner Violence Prevention in Uganda

Abstract: Research from Rakai, Uganda, suggests intimate partner violence (IPV) is common and attitudes condoning it are widespread. We used a public health approach to develop and implement an evidence-based IPV prevention intervention named the Safe Homes and Respect for Everyone (SHARE) Project. SHARE was designed on the Transtheoretical Model of behavior change and adapted IPV prevention strategies from Raising Voices and Stepping Stones. SHARE was implemented in four regions of Rakai. This article describes the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 32 publications
(59 reference statements)
1
49
1
Order By: Relevance
“…We engaged 40 resident community volunteers (10 per region) to work as local ambassadors of the project. In April and May 2005, the SHARE staff members underwent four weeks of training on IPV awareness and prevention, and provision of violence-related support (Wagman, et al, 2012; Wagman, et al, 2015). We rolled out intervention activities in June 2005 and they ran through December 2009.…”
Section: Intervention Design and Implementation (Steps 3a And 3b)mentioning
confidence: 99%
See 2 more Smart Citations
“…We engaged 40 resident community volunteers (10 per region) to work as local ambassadors of the project. In April and May 2005, the SHARE staff members underwent four weeks of training on IPV awareness and prevention, and provision of violence-related support (Wagman, et al, 2012; Wagman, et al, 2015). We rolled out intervention activities in June 2005 and they ran through December 2009.…”
Section: Intervention Design and Implementation (Steps 3a And 3b)mentioning
confidence: 99%
“…In this paper we explain how we used the four step CDC/VPA approach to integrate an IPV prevention intervention, called the Safe Homes And Respect for Everyone (SHARE) Project (Wagman, et al, 2012), into the existing HIV prevention, care and treatment infrastructure of the Rakai Health Sciences Program (RHSP). RHSP has conducted research on and provided services for HIV/AIDS and reproductive health in rural Uganda since 1988 (Wawer et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the community activism strategy SHARE appointed 40 community volunteers (CVs) - ten per each SHARE cluster – to help, on an ongoing basis, facilitate project activities and events (Wagman et al, 2012). Because CVs were resident members of their cluster they were able to recognize familiar and unfamiliar intervention participants.…”
Section: Practical and Ethical Challengesmentioning
confidence: 99%
“…Therefore, change is hypothesized as occurring over time or in stages rather than abruptly or all at once. An Ugandan study, utilizing the TTM with abused women and public health programs, found that individuals who are in the precontemplation stage of change do not intend to change in the next 6 months, but those who are in contemplation stage do intend to change in the next 6 months (Wagman et al, 2013). If the current study reached more individuals in the precontemplation stage of change, it is likely that behavioral change would be delayed but changes in perception could be detected sooner as an individual begins to shift into the contemplation stage.…”
Section: Risk and Safety Scores Between Groupsmentioning
confidence: 99%